Lacunary Statistical Convergence of Order \(α\) for Generalized Difference Sequences in Linear Partial Metric Space - Kumar, Manoj; Ritu; Gupta, Sandeep (Communications in Mathematics and Applications, 2024)
In the present study, with the use of generalized difference operator \(Δ^p\), we have the notion of \(Δ^p\)-lacunary statistical \(φ\)-convergence and \(Δ^p\)-lacunary strongly \(φ\)-Cesàro summability of order \(α\), in partial metric space \((X,φ)\), where \(φ\) is a partial metric on \(X\). We also analyse these notions with the fusion of modulus function. In addition we also establish some relationship between these concepts.